PENGARUH WAKTU PENUNDAAN TERHADAP KADAR GLUKOSA DARAH SEWAKTU DENGAN METODE POCT PADA MAHASISWA - NORMA FARIZAH FAHMI; NAILUFAR FIRDAUS; NIVIA PUTRI (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2020)
Glucose is the main energy source in living organisms. Handling the sample is one of the qualities that must be maintained when going to check blood glucose levels. Blood glucose checks should be done as soon as possible because delays in the time of examination will affect the results. The purpose of this study is to analyze the effect of time delay on blood glucose levels while using the POCT method on college students. This study used a quasi experiment design. This research was conducted in November 2018 until July 2019. The place of this research was carried out in the kimia Clinical Pathalogy Laboratory of S1 Ners Study Program. The variable used in this research was, namely the delay in the examination of blood glucose in the thattime and the dependent variable was an immediate blood glucose examination. The population is all of S1 Ners college students at the STIKes Ngudia Husada Madura. The sampling technique used was proportionate stratified random sampling with a total sample of were 26 respondent. The method used for blood glucose examination is Point of care testing (POCT). Data analysis used Repeated Anova with a level of confidence α = 0.05. The results of the Shapio-Wilk normality statistical test showed that the data were normally distributed with a significance of 0.280 (> 0.05) at immediate check, 0.744 (> 0.05) delay of 30 minutes, 0.713 (> 0.05) delay of 60 minutes, 0.173 (> 0.05) at a delay of 90 minutes. Then followed by the Repeated Anova test obtained a significance value of p = 0,000 <0,05. This indicates that there was an influence between the time delay on the blood glucose level of time with the POCT method on students.